Endocultivation: Histomorphological effects of repetitive rhBMP-2 application into prefabricated hydroxyapatite scaffolds at extraskeletal sites. Issue 6 (July 2015) - Beck-Broichsitter, Benedicta E.; Becker, Stephan T.; Seitz, Hermann; Wiltfang, Jörg; Warnke, Patrick H.
Abstract The timing of application of recombinant human bone morphogenic protein-2 (rhBMP-2) may be important in determining the final outcome of engineered bone tissue. This study investigates the impact of repetitive rhBMP-2 application on hard and soft tissue morphology in endocultivation. A 3D-printed scaffold was implanted into a pouch in the latissimus dorsi muscle in 40 Lewis rats. RhBMP-2 was injected at defined time points and animals received a total of 200 μg each. Control groups received either rhBMP-2 simultaneously with scaffold implantation, or solely a scaffold with no rhBMP-2. Fluorescence markers were injected after operation. CT-scans and histological examination were performed after 8 weeks. Multiple comparisons revealed significant differences of bone density between the groups who received delayed injections at two separate time points in time compared to those who had simultaneous rhBMP-2 application (p = 0.0038; p = 0.0063) and the control group (p = 0.017, p = 0.0284). The blood vessel count was significantly higher in groups with repetitive injections compared with both control groups. Two soft tissue types were identified and found to have different distributions in the different study groups. Fluorescence labeling showed active new bone formation after 4–5 weeks in all groups where rhBMP-2 was administered. Multiple repetitive injections were more effective than simultaneous application regarding bone density indicating time-dependent effects of rhBMP-2. Bone formation processes were detectable several weeks after rhBMP-2 application indicating long-term effects.